2021
DOI: 10.1021/acssynbio.0c00452
|View full text |Cite
|
Sign up to set email alerts
|

YESS 2.0, a Tunable Platform for Enzyme Evolution, Yields Highly Active TEV Protease Variants

Abstract: Here we describe YESS 2.0, a highly versatile version of the yeast endoplasmic sequestration screening (YESS) system suitable for engineering and characterizing protein/peptide modifying enzymes such as proteases with desired new activities. By incorporating features that modulate gene transcription as well as substrate and enzyme spatial sequestration, YESS 2.0 achieves a significantly higher operational and dynamic range compared with the original YESS. To showcase the new advantages of YESS 2.0, we improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…Our mammalian cell experiments developing a multiple input reporter suggested a strategy that could be used in high-throughput screening to identify proteases with altered substrate specificity. Many prior screens for reprogrammed proteases suggested a need for combining positive selection (where a mutant protease cleaving an altered substrate can be selected for) with negative counterselection (where proteases that still cleave the native cleavage substrate are selected against). ,,,, To explore this, we tested implementation of the multiple input reporters in yeast, which provide a versatile platform for high-throughput screening and are amenable to growth selection screens. , We envisioned using the same design as in mammalian cells, with a Gal4-VP16 transcription factor tethered to ER ligand binding domain (via a protease cleavage site) to trap the protein in the cytosol in the absence of protease. We could then insert a second cleavage site, specific to the native protease substrate, between Gal4 binding domain and VP16 activation domain, resulting in inactivation of the transcription factor upon cleavage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our mammalian cell experiments developing a multiple input reporter suggested a strategy that could be used in high-throughput screening to identify proteases with altered substrate specificity. Many prior screens for reprogrammed proteases suggested a need for combining positive selection (where a mutant protease cleaving an altered substrate can be selected for) with negative counterselection (where proteases that still cleave the native cleavage substrate are selected against). ,,,, To explore this, we tested implementation of the multiple input reporters in yeast, which provide a versatile platform for high-throughput screening and are amenable to growth selection screens. , We envisioned using the same design as in mammalian cells, with a Gal4-VP16 transcription factor tethered to ER ligand binding domain (via a protease cleavage site) to trap the protein in the cytosol in the absence of protease. We could then insert a second cleavage site, specific to the native protease substrate, between Gal4 binding domain and VP16 activation domain, resulting in inactivation of the transcription factor upon cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…Our work adds to the growing number of in vivo selection screens for engineering proteases, showing advantages in ease of use through use of a simple growth assay. An alternate yeast-based method, YESS/YESS2.0 (yeast endoplasmic reticulum sequestration screening), shows promise for improving protease enzyme kinetics but is a complicated system requiring endoplasmic reticulum trafficking and surface expression, antibody staining, galactose induction, tuning of protease expression using β-estradiol, a specialized transcription factor responsive to β-estradiol, and rounds of FACS-based cell sorting. , Other in vivo methods for evolving proteases with positive and negative selection include PACE (phage-assisted continuous evolution) and PANCE (phage-assisted noncontinuous evolution), which induce continuous expression of mutagenic genes. , While our methods cannot compete with PACE and PANCE phage-based evolution methods in their speed and depth of sampling protein diversity, these methods require the introduction of bacteriophage into lab environments, requiring additional care and challenges to avoid contamination, and some expertise in working with the system . Another limitation of the PACE systems, for some targets, is the noneukaryotic expression system used.…”
Section: Resultsmentioning
confidence: 99%
“…Paradigm 1 is exemplified by Olsen et al, who used the adsorption of a positively charged FRET (Forster Resonance Energy Transfer) substrate on the negatively charged cell surface to isolate, using FACS, an OmpT outer membrane protease mutant with altered specificity [45]. The same group later reported other examples [46][47][48] of this approach. Pitzler et al [49] reported an interesting variation wherein the presence of a hydrolase-glucose oxidase coupled activity leads to radical formation and polymerization of a fluorescent monomer on the surface of E. coli, leading to a "fur-shell" structure which can be FACS sorted.…”
Section: Optical Methods > Micro Scale Methods > Well Arrays Combined With Microscopymentioning
confidence: 99%
“…However, the biggest interest lies in the improvement of TEVp catalytic activity, since the wild type is slow compared to other widely used proteases that commonly implement serine as a nucleophile. To date, several directed evolution studies have yielded a handful of variants with up to an order of magnitude higher activity. , …”
Section: Introductionmentioning
confidence: 99%